Pengaruh Penerimaan Diri dan Religiusitas Terhadap Resiliensi Pada Pasien Kanker - Robertus Surjoseto; Devy Sofyanty (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
Resilience can be defined as the ability to flexibly respod to change situational need and ability to rise from a negative emotional experience. Everyone must have good resilience to avoid problem like happened cancer patients who have known they got depresion easily. People who have resilience will be more able to survive withtheir serious problems than people who do not have resilience. An important factor that can affect the resilience of person with cancer is self acceptance and religiosity. This research aims to examine and analyze the effect of self acceptance and religiosity on resilience at anxiety and depression on the quality of life of cervical cancer patients at cancer patient in the Hospital Dr. Cipto Mangunkusumo Jakarta. The research design uses a quantitative descriptive design, sampling technique using the purposive sampling used in this research were 50 persons. Data collection was carried out through questionnaires, interviews and observation. Data analysis using multiple linier regression. Based on the results of the research, it was concluded self acceptance and religiosity in patients cancer have affect the cancer patients resilience. From the result it recommended the strategies for cancer patient to increase self acceptance and religiosity to achieve positive adaptation to their disease.